2017
DOI: 10.1159/000463394
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Environmental Toxicants in Breast Milk and Rapid Infant Growth

Abstract: Background/Aims: Many environmental toxicants are passed to infants in utero and through breast milk. Exposure to toxicants during the perinatal period can alter growth patterns, impairing growth or increasing obesity risk. Previous studies have focused on only a few toxicants at a time, which may confound results. We investigated levels of 26 toxicants in breast milk and their associations with rapid infant growth, a risk factor for later obesity. Methods: We used data from the Norwegian HUMIS study, a multi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Fifteen studies examined growth in infants and children using various metrics and covering age ranges from newborn infants to children 18 y of age. Chemicals studied included polychlorinated dibenzodioxins (PCDDs), polychlorinated dibenzofurans (PCDFs), and/or PCBs (Criswell et al. 2017; Gladen et al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fifteen studies examined growth in infants and children using various metrics and covering age ranges from newborn infants to children 18 y of age. Chemicals studied included polychlorinated dibenzodioxins (PCDDs), polychlorinated dibenzofurans (PCDFs), and/or PCBs (Criswell et al. 2017; Gladen et al.…”
Section: Resultsmentioning
confidence: 99%
“…2014), polybrominated diphenyl ethers (PBDEs) (Wohlfahrt-Veje et al. 2014), and organochlorine pesticides, including DDT, dichlorodiphenyldichloroethylene (DDE), hexachlorobenzene (HCB), aldrin, heptachlor, β-hexachlorocyclohexane (β-HCH), α-HCH, and heptachlor epoxide (Criswell et al. 2017; Du et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When considering the impact of polychlorinated biphenyls (PCBs), trends found between human breast milk PCB concentrations and infant growth outcomes are conflicting. One study showed a correlation between increased breast milk levels of beta-hexachlorocyclohexane (β-HCH), an agricultural pesticide, at 1 month after birth and reduced infant weight gain up to age 6 months (Criswell et al 2017). However, another found no significant difference between infant growth measures at 6 months and 1 year and increased PCBs in human milk at 3 months postpartum (Pan et al 2010).…”
Section: Maternal Stressors and Exposures During Lactationmentioning
confidence: 99%